Examining the Relationship Between Work Alienation and Quality Perception in Nurses - Şule Kurt; Burcu Genç Köse; Havva Öztürk (Association of Nurse Managers, 2023)
Aim: This research was conducted to determine the relationship between the work alienation level and quality perceptions of nurses working in the hospital. Method: The population of this descriptive, correlational, and cross-sectional study consisted of 300 nurses working in a training and research hospital in a province of Turkey, and the sample consisted of 134 nurses who volunteered to participate in the study. Results: The nurses' mean score from the work alienation scale was 66.6 (SD=13.6), and their mean score from the quality perception scale was 257.7 (SD=50.6). A moderately negative and significant relationship was found between work alienation and quality perception scores (r=-0.64; p<0.001). Conclusion: The level of work alienation and quality perceptions of nurses is moderate. The work alienation level of nurses negatively affects their perceptions of quality, or as their alienation levels increase, their quality perceptions decrease. Organizational managers should use strategies and policies that will reduce the tendency of nurses to alienate from work. It is recommended that the study be repeated by other researchers by increasing the number of samples.